2022
DOI: 10.1186/s12870-021-03411-w
|View full text |Cite
|
Sign up to set email alerts
|

Fruit ripening: dynamics and integrated analysis of carotenoids and anthocyanins

Abstract: Background Fruits are vital food resources as they are loaded with bioactive compounds varying with different stages of ripening. As the fruit ripens, a dynamic color change is observed from green to yellow to red due to the biosynthesis of pigments like chlorophyll, carotenoids, and anthocyanins. Apart from making the fruit attractive and being a visual indicator of the ripening status, pigments add value to a ripened fruit by making them a source of nutraceuticals and industrial products. As … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 104 publications
(53 citation statements)
references
References 246 publications
(200 reference statements)
4
49
0
Order By: Relevance
“…Fruit ripening is a highly variable process with numerous differences when different plant species are compared; however ripening is often characterized by the accumulation of pigments, such as carotenoid sand anthocyanins (Figure 5) [56]. Despite these differences, fruit ripening has been classified into two distinct groups, climacteric and non-climacteric, which differ in their patterns of ethylene production and respiration at the onset of the ripening process [57,58].…”
Section: Final Ripening Stages Of Mature Cherrymentioning
confidence: 99%
“…Fruit ripening is a highly variable process with numerous differences when different plant species are compared; however ripening is often characterized by the accumulation of pigments, such as carotenoid sand anthocyanins (Figure 5) [56]. Despite these differences, fruit ripening has been classified into two distinct groups, climacteric and non-climacteric, which differ in their patterns of ethylene production and respiration at the onset of the ripening process [57,58].…”
Section: Final Ripening Stages Of Mature Cherrymentioning
confidence: 99%
“…Fruit still has to undergo a series of physiological changes, such as ripening, aging, and death after harvest, and still changes the internal material through respiration. Previous studies showed that in the process of fruit ripening, the metabolism of reactive oxygen species was strengthened, which would produce a toxic effect on cells and lead to the destruction of cell membrane structure [ 43 ]. Therefore, during the process from fresh fruit to two days after harvest, the fruit of noni was still undergoing complex physiological activities.…”
Section: Discussionmentioning
confidence: 99%
“…Fruit ripening results in color changes due to biosynthesis, degradation and appearance of pigments, events catalyzed by enzymes activated at this stage of fruit development (Kapoor et al, 2022).…”
Section: Skin Color Weight Loss and Respiratory Activity Of Fruits Pi...mentioning
confidence: 99%